2013
DOI: 10.1021/jo402414k
|View full text |Cite
|
Sign up to set email alerts
|

C═N-Containing Azaarenes as Activating Groups in Enantioselective Catalysis

Abstract: Nitrogen-containing aromatic heterocycles (azaarenes) are of widespread chemical significance, and chiral compounds containing azaarenes feature prominently in pharmaceuticals, agrochemicals, and natural products. ThisPerspective highlights the use of a relatively underdeveloped strategy to prepare chiral azaarene-containing compounds: exploitation of the C=N bond embedded within certain azaarenes to activate adjacent functionality in catalytic asymmetric reactions. Work in this area has resulted in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 150 publications
1
88
0
4
Order By: Relevance
“…[2][3][4] In this context, we have reported 1b the enantioselective rhodium-catalyzed 1,4-arylation [5][6][7][8] of β-substituted alkenylazaarenes with arylboronic acids using a secondary amide-containing chiral diene 9-11 ligand L1 (see Table 1, entry 1), which builds upon early studies by the groups of Lautens 12a and Genet 12b using vinylazaarenes. Although L1 was highly effective, it was of interest to determine whether a ligand of this complexity, possessing stereochemical elements additional to those of the chiral diene component, was actually necessary for optimal results.…”
mentioning
confidence: 98%
“…[2][3][4] In this context, we have reported 1b the enantioselective rhodium-catalyzed 1,4-arylation [5][6][7][8] of β-substituted alkenylazaarenes with arylboronic acids using a secondary amide-containing chiral diene 9-11 ligand L1 (see Table 1, entry 1), which builds upon early studies by the groups of Lautens 12a and Genet 12b using vinylazaarenes. Although L1 was highly effective, it was of interest to determine whether a ligand of this complexity, possessing stereochemical elements additional to those of the chiral diene component, was actually necessary for optimal results.…”
mentioning
confidence: 98%
“…[15] We have already reported that ac hiral macrocyclic crown ether, binaphtho-34-crown-10 (34-C-10), could be used to form an effective asymmetric environment around the potassium cation of KHMDS.W eh ave also shown that catalytic asymmetric direct-type 1,4-addition reactions of simple amides,p romoted by K/34-C-10, can be achieved with high enantioselectivities. [15] We have already reported that ac hiral macrocyclic crown ether, binaphtho-34-crown-10 (34-C-10), could be used to form an effective asymmetric environment around the potassium cation of KHMDS.W eh ave also shown that catalytic asymmetric direct-type 1,4-addition reactions of simple amides,p romoted by K/34-C-10, can be achieved with high enantioselectivities.…”
mentioning
confidence: 99%
“…Vinyl azines are isostructural with respect to α,β-unsaturated carbonyl compounds and, as described in the review literature (53), display analogous reactivity. However, their use as pronucleophiles in catalytic reductive coupling has only recently begun to be explored.…”
Section: Acrylates Enones and Vinyl Azinesmentioning
confidence: 92%